FLEXURAL PROPERTIES OF OIL PALM WOOD BASED GLUE LAMINATED TIMBER USING FINITE ELEMENT METHOD - Hackel, Martin (World Conference on Timber Engineering (WCTE 2023))
The anatomical structure of oil palm wood is only to a limited extent comparable to common wood species used in construction. Typical for monocotyledons, the material is composed of high density vascular bundles and a parenchymatous tissue of lower density. In three experiment sets, the local and global moduli of elasticity (MOE) and the flexural strength of oil palm wood based GLT are determined using FEM and various influencing parameters are investigated in a sensitivity analysis. Furthermore, the application of densified tension lamellas is studied. The results of the modelling are compared with the results from mechanical tests. Significant differences, mainly attributed to the specific parameters of the selected material, are observed. The results of this preliminary study serve as a starting point for computer-aided optimisation and modelling of other oil palm-based products.
Keywords: Oil palm wood; finite element method (FEM); GLT; modulus of elasticity; flexural strength